2015
DOI: 10.1111/ajo.12376
|View full text |Cite
|
Sign up to set email alerts
|

Success factors for Bakri balloon usage secondary to uterine atony: a retrospective, multicentre study

Abstract: The use of the Bakri™ balloon method, if undertaken early, is effective for the management of PPH with uterine atony (100% success compared to 69% overall success rate). Intrauterine balloon tamponade should included in PPH management guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
2
17
3
Order By: Relevance
“…The data demonstrated that presence of coagulopathy and placenta accreta, as well as higher blood loss at the time of balloon insertion and higher drainage volume from the uterine cavity within the first 30 minutes were negatively associated with the success of IUBT. Despite arguments against the “paradoxical” use of IUBT with uterine atony to expand rather than contract the uterus, most studies show that the method was equally effective for managing PPH due to uterine atony as for placental site bleeding . In the present study, we were unable to show any significant difference in the success rate between placenta previa and uterine atony patients, with success rates of 69.8% (37/53) and 76.0% (19/25), respectively.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The data demonstrated that presence of coagulopathy and placenta accreta, as well as higher blood loss at the time of balloon insertion and higher drainage volume from the uterine cavity within the first 30 minutes were negatively associated with the success of IUBT. Despite arguments against the “paradoxical” use of IUBT with uterine atony to expand rather than contract the uterus, most studies show that the method was equally effective for managing PPH due to uterine atony as for placental site bleeding . In the present study, we were unable to show any significant difference in the success rate between placenta previa and uterine atony patients, with success rates of 69.8% (37/53) and 76.0% (19/25), respectively.…”
Section: Discussioncontrasting
confidence: 82%
“…Despite arguments against the "paradoxical" use of IUBT with uterine atony to expand rather than contract the uterus, most studies show that the method was equally effective for managing PPH due to uterine atony as for placental site bleeding. 19,20 In the present study, we were unable to show any significant difference in the success rate between placenta previa and uterine atony patients, with success rates of 69.8% (37/53) and 76.0% (19/25), respectively.…”
Section: Discussioncontrasting
confidence: 70%
“…Intrauterine balloon tamponade, arterial embolization, arterial ligation and uterine compression sutures have all been reported to be effective in stopping hemorrhage and preventing hysterectomy [40][41][42][43][44][45][46][47][48][49][50][51]. Yet, if unsuccessful, these interventions may also delay hysterectomy, especially because they are performed with low frequency, and thus, experience with these techniques may be insufficient.…”
Section: Improving Maternal Outcomes: Obstetric Interventions To Stopmentioning
confidence: 99%
“…There is no clear evidence on how long the tamponade should be left in place, but its effects can be observed after 4-6 h in most cases. In a small case series, success rates of uterine balloon catheters for controlling hemorrhage ranged from 57% after cesarean delivery to 100% after vaginal delivery [50,51].…”
Section: Uterine Balloon Tamponadementioning
confidence: 99%